PENINGKATAN KETERAMPILAN GURU RAUDHATUL ATHFAL DALAM MENCIPTAKAN SENAM KREASI MELALUI PROGRAM PELATIHAN - Syamsudin, Moh Anas; Andriani, Viena Wanidha (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2024)
Gymnastics has become a routine activity carried out by teachers and children at the PAUD institution. Gymnastics activities that are attached to PAUD often lead to competitions. Gymnastics competitions for early childhood are usually creative, that is, teachers or students are directed to create gymnastic movements based on their creations. However, most teachers only imitate existing gymnastics movements without being able to create their own. Based on the results of the observations carried out in August 2023 at the location of the creative gymnastics competition for RA children in Tegaldlimo Banyuwangi District, 7 of RA Institutions that took part, almost all of them used existing gymnastics movements. The aim of this community service (PKM) is to improve the skills of RA teachers in Tegaldlimo Banyuwangi District in creating and implementing creative exercises that are interesting and beneficial for young children. The method used in PKM is service learning. The result of this PKM activity is the increase of RA teachers’ skill in creating gymnastics creations for early childhood in Tegaldlimo Banyuwangi District. This improvement in teacher skills can be seen from the results of the pretest and posttest scores based on 3 indicators, namely, 1) understanding the concepts with an average pretest score of 13.08 and posttest of 35.38. 2) composing the music with an average pretest score of 1.58 and posttest of 2.58. 3) creating the gymnastic movements with an average pretest score of 1.16 and posttest of 2.84. The intention of this PKM program is inviting the RA teachers in Tegaldlimo District, Banyuwangi, to make exercise videos that are created by themselves and apply it to learning activities in their respective institutions.